Analytical solution of the cauchy problem for a nonstationary threedi-mensional model of the filtration theory - Rakhymova, Aigerim T.; Gabbassov, Mars B.; Ahmedov, Anvarjon A. (Penerbit Akademia Baru, 2021)
This paper is devoted to the study of the Cauchy problem for a system of differential equations describing the unsteady flow of a compressible fluid in a homogeneous and inhomogeneous porous medium with a general nonlinear filtration law in threedimensional space. In the work using the methods of four-dimensional mathematics, a special four-dimensional space was developed, as well as a functional space of regular functions, and analytical conditions were obtained on the general form of the nonlinear filtration law for which the Cauchy problem has a solution.